Heart transplantation surgery in children and young adults with congenital heart disease - Sabrina Martens; Hongtao Tie; Hans Gerd Kehl; Tonny DT Tjan; Hans Heinrich Scheld; Sven Martens; Andreas Hoffmeier (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Pediatric cardiac transplantation remains a surgical challenge as a variety of cardiac and vessel malformation are present in patients with congenital heart disease (CHD). Despite limited availability and acceptability of donor hearts, the number of heart transplantations remains on a stable level with improved survival and quality of life. Observation As treatment options for CHD continue to improve and the chances of survival increase, more adult CHD patients are listed for transplantation. This review focuses on the clinical challenges and modified techniques of pediatric heart transplantations. Conclusion Not only knowledge of the exact anatomy, but above all careful planning, interdisciplinary cooperation and surgical experience are prerequisites for surgical success.